STRUCTURAL CHANGES AND EMPLOYMENT DYNAMICS OF SERBIAN POPULATION - Svjetlana Janković Šoja; Radojka Maletić (Ekonomika Poljoprivrede (1979), 2011)
Analysis of active population dynamics is necessary from an economic point of view since only that part of the population participates in the creation of economic value. During the reference period, a significant employment decrease was recorded in Serbia, which is caused by political and economic changes. Namely, according to some structures, analysis of the employment indicated a reduction in the gap in gender structure of employees, change of image of the economic structure (agriculture and manufacturing industry recorded a significant decline in activity), and employment structure based on professional qualifications indicates the highest percentage of employees with secondary education.